Knock at the door and other baby action rhymes - Chorao, Kay (Dutton Children's Books, 1999)
Includes such rhymes as "Five Little Sparrows," "Pat-a-Cake," "Giddyap Horsey," and "Bunnies' Bedtime" with illustrations showing the actions that should be used with each one.